CELLO AS A LANGUAGE TEACHING METHOD IN INDUSTRIAL REVOLUTION 4.0 ERA - Halimah Halimah; Gufran Ali Ibrahim; Ninuk Lustyantie (University of Kuningan, 2018)
CELLO is derived from Community English Language Learning and Orai. It is a new teaching method developed especially in the community of English language learning based on the idea of Curran’s work on teaching method. CELLO is a combination between an innovative teaching method and media technology called Orai Application that is applied in teaching and learning of speaking especially in fostering students’ fluency. Today, all graduates face a world transformed by technology, in which the Internet, cloud computing, and social media create different opportunities and challenges for formal education systems. This paper aims to explore the use of CELLO in assisting student’s speaking fluency. This classroom action research consists of three cycles in which each cycle consists of six stages, namely identify the problem, data gathering, data interpreting, action on evidence, evaluation, and revision. The obtained data showed that CELLO method could improve students’ speaking fluency. Based on the finding, implementing CELLO method is strongly recommended in teaching speaking especially at fostering students’ speaking fluency.Keywords: CELLO; speaking fluency; technology 4.0; industrial revolution; action research.